The Effect of Perceived Cost, Trust, Usefulness, And Customer Value Addition on Intention to Use of Go-Pay Mobile Payment Services In Small Traders - Handri Mufti Nirmawan; Winny Astiwardhani (Profesional Muda Cendekia Publishing, 2021)
This research is based on the phenomenon of the problem of the widespread use of payment methods based on financial technology (fintech), namely mobile payments which contribute to the circulation of electronic money reaching Rp.47.2 trillion in December 2018. However, there are mental barriers that increasingly hinder the intention to adopt this fintech-based service. One of the largest providers of mobile payment is Go-Pay who owned by Go-Jek. These barriers are in the form of costs, trustworthiness, usefulness, benefits, and experiences that will be obtained. The aims of this study are to identify the effects of Perceived cost, Perceived trust, Perceived usefulness, and Perceived customer value addition on Intention to Use Go-Pay Mobile Payment services on Small Traders. The samples used were 120 respondents of small traders. This study uses multiple linear regression analysis to identify the relationship between variables. These results indicate that the perceived cost, perceived trust, and perceived customer value addition have a significant positive effect on Intention to use, while perceived usefulness has a negative and insignificant effect on Intention to use. This research is expected to be able to provide benefits for mobile payment providers in developing ways to attract small merchant partners for their mobile payment facilities.